Strategi Keunggulan Bersaing Melalui Orientasi Pasar Dan Inovasi Produk Kartu E-Money Untuk Peningkatan Kinerja Pemasaran - Agyl Handira Ishaq (Sekolah Pascasarjana Perbanas Jakarta, 2020)
This study discusses the Competitive Advantage Strategy through Market Orientation and Innovation of E-Money Card Products at Bank Mandiri Jakarta Head Office for Improving Marketing Performance. The sample used in this study were students using Bank Mandiri e-money products located in the Perbanas Institute Jakarta academic community. The sampling technique used in this study was the purposive sampling method. Methods of collecting data using a questionnaire with a Likert scale 1-10. Data analysis techniques were using the Structural Equation Modeling (SEM) AMOS program version 21.0. The results showed that the Market Orientation on competitive advantage and marketing performance did not positively affect. For product innovation variables have a significant positive effect on competitive advantage. However, product innovation variables do not have a significant positive effect on marketing performance. Then competitive advantage has a significant positive effect on the performance of marketing of Bank Mandiri e-money products.